INVESTMENT PORTFOLIO MODELER - RHANDHAWA, HARVINDER SINGH (IRC, 2019)
There have been countless cases of bad investment decisions done and questions that arise regarding where the average investor puts their money in. The combination of these 2 issues has given birth to titanic errors such as major portfolio loss and less efficient markets. Billions of dollars’ worth of money have been wiped out from the economy due to the wrong investment decisions, FOMO events and biased investment advice. A bias free, statistic based predictive model needs to be developed to fill in a vacuum of need created by inefficient behavior in the stock market.